2018
DOI: 10.3390/ijerph15122890
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Life Expectancy and Its Association with Economic Factors in the Belt and Road Countries—Evidence from 2000–2014

Abstract: In 2013, China launched the Belt and Road (B&R) Initiative in an effort to promote trade and economic collaboration. This study examined the change in life expectancy (LE) among countries along B&R and studied the impact of economic development on LE. Data from 65 B&R countries from 2000 to 2014 were compiled and analyzed. Trend of LE was examined by sex and country. Linear quantile mixed model was used to study the associations between LE and economic factors. In 2014, the average LE in all B&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…Our findings related to per capita income, the third most relevant socioeconomic factor in this research, are consistent with previous literature [ 25 , 34 , 124 ]. In effect, higher per capita income affects health status improving nutrition, access to health care and working conditions.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings related to per capita income, the third most relevant socioeconomic factor in this research, are consistent with previous literature [ 25 , 34 , 124 ]. In effect, higher per capita income affects health status improving nutrition, access to health care and working conditions.…”
Section: Discussionsupporting
confidence: 93%
“…Following previous specialized literature, we first considered two “classic” socioeconomic variables included in the empirical research referred to the determinants of health status: per capita income [ 12 , 22 , 24 , 25 , 26 , 124 ] and education [ 13 , 30 , 31 , 90 , 125 ]. Higher incomes are expected to result in better health outcomes by improving access to food, shelter and hygiene [ 25 , 34 , 124 ]. In the same way, higher levels of education are expected to improve health outcomes by supporting better decision-making abilities and increasing knowledge of preventive care behaviors [ 30 , 31 , 125 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unemployment is also analyzed [11,12,13] as a determinant of the health status of the population as a representative measure of the fluctuations of the economic cycle. Other relevant macroeconomic variables used in this type of analysis are inflation [14] and gross capital [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Boachie (2017) confirmed that good health represented by life expectancy has a significant and positive impact on real GDP. Significant gender inequalities in longevity were identified and confirmed by many authors such as Bai et al (2018), Belon et al (2014), Clark and Peck (2012), Sandiford (2009) or Van Oyen et al (2010). The fact that women show more positive outcomes in life expectancy is well known (Andrade et al, 2011;Haeberer et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 87%